2011
DOI: 10.3109/14992027.2011.572263
|View full text |Cite
|
Sign up to set email alerts
|

Open ear hearing aids in tinnitus therapy: An efficacy comparison with sound generators

Abstract: TRT was equally effective with sound generator or open ear hearing aids: they gave basically identical, statistically indistinguishable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 14 publications
2
85
0
7
Order By: Relevance
“…For example, Schaette et al [2010] reported that hearing aids and noise devices can lead to a significant reduction in tinnitus loudness not only during device usage, but also when the device was switched off. Parazzini et al [2011] also reported a significant reduction in tinnitus loudness in bilateral open-fit hearing aid users, when they were asked to judge the average tinnitus loudness over the past month. Interestingly, bilateral sounds generators were as effective as hearing aids, suggesting that a 'tinnitus gain mechanism' in the auditory system might be sensitive simply to the overall level of input.…”
Section: Clinical Relevance Of Abnormal Neural Activitymentioning
confidence: 99%
“…For example, Schaette et al [2010] reported that hearing aids and noise devices can lead to a significant reduction in tinnitus loudness not only during device usage, but also when the device was switched off. Parazzini et al [2011] also reported a significant reduction in tinnitus loudness in bilateral open-fit hearing aid users, when they were asked to judge the average tinnitus loudness over the past month. Interestingly, bilateral sounds generators were as effective as hearing aids, suggesting that a 'tinnitus gain mechanism' in the auditory system might be sensitive simply to the overall level of input.…”
Section: Clinical Relevance Of Abnormal Neural Activitymentioning
confidence: 99%
“…Two factors related to tinnitus are important and should be differentiated: the intensity of the tinnitus symptoms and the discomfort caused to the patient's life 25 . After the use of the prosthesis the discomfort level decreased significantly in the studied sample, and research 26,27 shows that the combined use of amplification and sound generators for the relief of bothersome tinnitus seemed to be more efficient than pure amplification, and that this reduction may be observed progressively from the third month of use of the devices 28 .…”
Section: Discussionmentioning
confidence: 90%
“…Für die Tinnituseffektivität (Übersicht in [58]) von konventionellen Hörgeräten liegen nur Arbeiten mit mäßigen oder schwachen Evidenzstärken vor [34,52,61,70]. Zudem sind die Ergebnisse widersprüch-lich.…”
Section: Materials Und Methodenunclassified